Pain assessment tools: A literature review - Michalczewska, Aneta; Wierzejska, Natalia; Pach, Magdalena; Fugas, Agnieszka; Nowak, Agnieszka; Chmielowiec, Zuzanna; Partyka, Alicja; Dziedzic, Mariola; Smykiewicz, Karolina; Dobrzańska, Justyna (Journal of Education, Health and Sport, 2024)
Pain is a major factor expressed by hospital patients and is the main reason they seek medical help. Evidence suggests that children experiencing pain often do not receive optimal pain assessment and relief. This article refers to a literature review discussing tools and management strategies for assessing children's pain. It concludes that implementing an educational program for medical professionals could enhance their awareness of best practices in pain assessment and management guidelines.